Students' Mathematical Thinking Process in Solving Mathematical Problems in terms of Keirsey's Personality Type - Mentari Diyin Ari Agustin (Madrosatuna: Journal of Islamic Elementary School, 2018)
The study aims to desdescribe the process of thinking of students in solving mathematical problems in accordance with keirsey personality types, namely guardian, artisan, rational and idealist. The method in this study uses descriptive qualitative. Data collection technique in this study are observation, interviews, mathematical thinking test (TBM) using fractions. From the result of the study, the guardian, Artisan, Rational an Idealist type students all indicators of mathematical thingking, namely relationship, statements, communication, reasoning nd evidence and problem solving have been seen even though not yet in full. However, what is more visible is the Artisan personality type, after that the rational and guardian types. Idialist type is the type of personality that most often does not appear as a whole.